Do flame retardant chemicals increase the risk for thyroid dysregulation and cancer?. Issue 1 (January 2017) - Hoffman, Kate; Sosa, Julie A.; Stapleton, Heather M.
Abstract : Purpose of review: Flame retardant chemicals are added to consumer products to reduce fire incidence and severity; approximately 1.5 million tons of these chemicals are used annually. However, their widespread use has led to their ubiquitous presence in the environment and chronic accumulation in human tissues. We summarize current trends in human flame retardant chemical exposure, and review recent data highlighting concerns for thyroid dysregulation and cancer risk in human populations. Recent findings: Polybrominated diphenyl ethers were once commonly used as flame retardant chemicals, but recently were phased out. Exposure is associated with thyroid dysregulation (mainly T4 reductions) in animals, with new work focusing on specific mechanisms of action. Polybrominated diphenyl ethers also impact human thyroid regulation and are related to clinical thyroid disease, but associations appear both dose and life-stage dependent. Emerging data suggest that common alternate flame retardant chemicals may be more potent thyroid disruptors than their predecessors, which is particularly concerning given increasing levels of exposure. Summary: Potential health impacts of flame retardant chemicals are only beginning to be understood for 'legacy flame retardant chemicals' (i.e., polybrominated diphenyl ethers), and are largely unevaluated for newer-use chemicals. Cumulatively, current data suggest impact on thyroid regulation is likely, potentially implicating flame retardant chemicals in thyroid disease and cancers for which thyroid dysregulation impacts risk or prognosis.